How to explain the campaign to revoke Lima Metropolitana’s mayor, Susana Villarán? An hypothesis about power and politics in the capital - Cavero Cornejo, Omar (2013)
The present essay attempts to explain the formation of a sector who leaded the campaign to revokeLima Metropolitana’s mayor, Susana Villarán, in 2013. The analysis focuses on the nature of power relations, within which institutions, actors, interests and chances of action are constituted. Our hypothesis is that the conglomerate of interests that organized for this purpose reveals a type of power organization in a network way: a flexible structure of links between people, groups and organizations, around different resources, one of which is State access. Sectors that led the «Yes» campaign express, rather than ideological differences, some networks resistance, bothered by management actions.